HARGA DIRI, KEMATANGAN KARIR DAN GENERASI Z - Mayasari, Endah (Universitas Tanjungpura, 2025)
The unemployment rate among Generation Z in Indonesia remains a strategic concern, with 9.9 million individuals classified as Not in Employment, Education, or Training (NEET) in 2024. In addition to the mismatch between education and industry needs, low career maturity has emerged as a major contributing factor. This study aims to analyze the influence of self-esteem on career maturity among Generation Z in Indonesia. A quantitative approach with an explanatory research design was employed. A total of 235 respondents participated in an online survey, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The findings reveal that self-esteem has a positive and significant effect on career maturity, with a path coefficient of 0.762 and an R ² of 0.580. These results reinforce career psychology theories, emphasizing that psychological factors such as self-confidence and self-acceptance play a critical role in career readiness. This study offers both theoretical contributions to human resource management and practical insights for designing psychosocial-based employment policies.